Seeking justice elsewhere: informal and formal justice in the true crime podcasts Trace and The Teacher’s Pet - Pâquet, Lili (Crime, media, culture, 2021)
Following Carol Smart?s argument that feminists have reason to mistrust legal institutions and to seek justice elsewhere, this article suggests that contemporary Australian true crime podcasts offer women and their families alternatives to seek justice beyond formal systems. This article will examine the representation of women in two recent and popular Australian true crime podcasts that followed inconclusive investigations of murder cases. Trace (2017?2018) is a seven-episode true crime podcast by Rachael Brown for the ABC about the 1980 murder of Maria James in her Melbourne bookshop, where she lived with her two sons. The Teacher?s Pet by Hedley Thomas for The Australian is about the disappearance of Lynette Dawson from the northern beaches of Sydney in 1982, leaving behind her two daughters. Thomas explicitly accuses Dawson?s husband, former professional rugby player, Chris Dawson, of murdering her and disposing of her body. Both true crime podcasts represent women in ways that?while not always feminist?use the affordances of mass media to draw support from the public, effectively inviting the audience to perform as an alternate jury. In both cases, this jurified audience has then engendered changes in formal processes.